Enhancing the electrochemical performance of Li2MnSiO4 cathode by manipulating the cathode-electrolyte interphase with triphenylphosphine oxide additive. (10th July 2020) - Liao, Kaisi; Huang, Ting; Feng, Yiming; Zhu, Hai; Wei, Weifeng; Zhang, Shiying
Abstract: As a kind of promising cathode material for high specific energy Li-ion batteries, Li2 MnSiO4, suffer from low reversible capacity and short cycle life, in part because of the inferior cathode electrolyte interphase film. Herein, triphenylphosphine oxide (TPPO) is adopted as a film-forming electrolyte additive to significantly upgrade the rate capability and cycling property of Li2 MnSiO4 at room temperature. With 2 wt% TPPO in the electrolyte, the Li2 MnSiO4 cathode exhibits the best electrochemical performance, which can provide a discharge capacity of 208.3 mAh g −1 and retain the 70.7% of initial capacity after 100 cycles at 0.5C, while the Li2 MnSiO4 cycled in baseline electrolyte is only 188.1 mAh g −1 and 33.5%. Moreover, the weakened polarization and improved coulombic efficiency of Li2 MnSiO4 in the electrolyte with TPPO at various rates are also displayed in this paper. The significant enhancement of Li2 MnSiO4 cathode is attributed to the excellent cathode electrolyte interfacial film formed through priority decomposition of TPPO on the surface of Li2 MnSiO4, which effectively suppresses continual electrolyte decomposition and Mn 2+ dissolution as well as increases Li-ion diffusivity. Eventually, the application of TPPO additive in the electrolyte can remarkably stabilize the structural integrity of Li2 MnSiO4 cathode and mitigate the capacity degradation. Graphical abstract: Image 1 Highlights: Triphenylphosphine oxide (TPPO) as a film formation additive to ameliorate the performance of Li2 MnSiO4 cathode. The decomposition of the TPPO additive to generate a high-quality electrolyte interphase film on the Li2 MnSiO4 surface. The interphase film generated in the electrolyte containing TPPO protects the cathode and facilitates charge transfer. The Li2 MnSiO4 cathode cycling in electrolyte with 2 wt% TPPO exhibits improved rate capability and cycling performancee. The cell with 2 wt% TPPO shows a capacity of 208.3 mAh g −1 and a capacity retention of 70.7% after 100 cycles at 0.5 C.